Plano de gestão do patrimônio arqueológico para os municípios de Narandiba, Presidente Prudente e Iepê, São Paulo, Brasil - Montardy, Lisandra Hernández [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
O patrimônio arqueológico, assumido como vestígios únicos e não renováveis, que expressam o modo de vida das populações pretéritas, constitui parte da realidade sociocultural vivenciada pelas sociedades atuais. Esta tese de doutorado contribui para melhorar a gestão do patrimônio arqueológico nos municípios de Narandiba, Presidente Prudente e Iepê, São Paulo, Brasil, ao dotar à prefeitura municipal de um documento norteador do estado da gestão do patrimônio arqueológico no município, que define as possíveis ações a serem tomadas para lograr uma adequada gestão, subsidiando diversas etapas da criação do plano municipal de gestão do patrimônio arqueológico. A pesquisa apresenta uma metodologia, que define um conteúdo para avaliar a criação de planos municipais de gestão do patrimônio arqueológico, a partir do emprego do método dialético-materialista e da aplicação de instrumentos da perspectiva sociocultural e da arqueologia. Uma adequada gestão do patrimônio arqueológico só é possível a partir de uma visão integral, que promova a cooperação entre todos os atores envolvidos e garanta apropriação social deste patrimônio e dos conhecimentos existentes sobre o mesmo.

The archaeological heritage, assumed as unique and non-renewable vestiges that express the way of life of past populations, constitutes part of the sociocultural reality experienced by current societies. This doctoral thesis contributes to improving the management of archaeological heritage in the municipalities of Narandiba, Presidente Prudente and Iepê, São Paulo, Brazil, by providing the municipal government with a document that guides the state of archaeological heritage management in the municipality, which defines the possible actions to be taken to achieve an adequate management, subsidizing several stages of the creation of the municipal plan for the management of the archaeological heritage. The research presents a methodological construct that defines the content to be evaluated for the creation of municipal plans for the management of archaeological heritage, based on the use of the dialectical-materialist method and the application of instruments from the sociocultural perspective and from archeology. Affirming that it is only possible to achieve an adequate management of the archaeological heritage from an integral vision, which promotes cooperation between all the actors involved and guarantees social appropriation of this heritage and of the existing knowledge about it.
Archaeological heritage management plan for the municipalities of Narandiba, Presidente Prudente and Iepê, São Paulo, Brazil
Keywords: Patrimônio arqueológico; Gestão patrimonial municipal; Archaeological heritage; Municipal heritage management